2011
DOI: 10.1007/s00253-011-3163-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli and bacteriophage T4 by high levels of dissolved CO2

Abstract: Little information is available regarding the effectiveness of water disinfection by CO(2) at low pressure. The aim of this study was to evaluate the use of high levels of dissolved CO(2) at 0.3-0.6 MPa for the inactivation of microorganisms. Bacteriophage T4 was chosen as the model virus and Escherichia coli was selected as the representative bacterium. The results of the study showed a highly effective log inactivation of E. coli and bacteriophage T4 at low and medium initial concentrations by high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…Some authors concluded that decompression rate is an important factor in inactivation due to the expansion of CO 2 into the cells (Fraser, 1951;Lin et al, 1992aLin et al, , 1992bKumugai et al, 1997;Cheng et al, 2011), while others found that it had no significant effect on bacterial inhibition and that mechanical cell bursting did not take place (Li et al, 2013;Debs-Louka et al, 1999;Nakamura et al, 1994;Vo et al, 2013a). Enomoto et al (1997b) found that explosive depressurization with pressures over 4 MPa had a strong effect on inhibition, but not at less than 4 MPa.…”
Section: Treatment Time Pressure Cycling Microbial Type Depressurimentioning
confidence: 96%
See 3 more Smart Citations
“…Some authors concluded that decompression rate is an important factor in inactivation due to the expansion of CO 2 into the cells (Fraser, 1951;Lin et al, 1992aLin et al, , 1992bKumugai et al, 1997;Cheng et al, 2011), while others found that it had no significant effect on bacterial inhibition and that mechanical cell bursting did not take place (Li et al, 2013;Debs-Louka et al, 1999;Nakamura et al, 1994;Vo et al, 2013a). Enomoto et al (1997b) found that explosive depressurization with pressures over 4 MPa had a strong effect on inhibition, but not at less than 4 MPa.…”
Section: Treatment Time Pressure Cycling Microbial Type Depressurimentioning
confidence: 96%
“…Moreover, an increase of pressure, temperature, or treatment time of CO 2 under pressure enhanced the antimicrobial effect against E. coli (Kamihira et al, 1987;Dillow et al, 1999;Wu et al, 2007;Kobayashi et al, 2007Kobayashi et al, , 2009bGarcia-Gonzalez et al, 2010). Thus the use of pressurized CO 2 has been widely investigated (Wu et al, 2007;Kobayashi et al, 2007Kobayashi et al, , 2009aJung et al, 2009;Garcia-Gonzalez et al, 2010;Klangpetch et al, 2011;Cheng et al, 2011).…”
Section: Gram-negative Bacteria Inactivation (Escherichia Coli)mentioning
confidence: 98%
See 2 more Smart Citations
“…Supercritical pressure up to 10 MPa and high temperature (55°C) were reported to effectively inactivate E. coli and coliforms -498 - (Kobayashi et al, 2009). However, Cheng et al (2011) concluded that pH was not related to the inactivation mechanism of dissolved CO 2 , which differed from the results of previous studies (Ballestra et al, 1996;Dillow et al, 1999;Hong and Pyun, 1999;Garcia-Gonzalez et al, 2007). Therefore, this study was conducted to investigate the inactivation of pathogenic bacteria (E. coli) and viruses T4 (double-stranded DNA) and MS2 (single-stranded RNA) by CO 2 .…”
Section: Introductionmentioning
confidence: 99%